Graphite phase carbon nitride doped bismuth oxide composite electrode material and preparation method and application thereof
By using graphite phase carbon nitride doped bismuth oxide composite electrode material, the existing capacitive deionization technology is solved, and the problem of low efficiency and poor stability when removing chloride and sodium ions in water is achieved, achieving efficient and low-cost cyclic desalination effect.
Patent Information
- Application Number
- CN202510055335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
When removing chloride and sodium ions in water, existing capacitive deionization technology has problems such as low ion removal efficiency, poor material stability and insufficient adsorption selectivity.
The graphite phase carbon nitride doped bismuth oxide (g-C3N4@Bi2O3) composite electrode material was used to prepare the material by high-temperature calcination method, which increased its specific surface area and specific capacitance, and enhanced the adsorption activity on Cl- and Na+ plasmas.
It significantly improves the electro-adsorption capacity and cyclic stability, and can efficiently remove chloride and sodium ions in water at low voltages, achieve cyclic desalination, and is cheap.
Smart Images

Figure CN119833319A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of capacitive deionization and desalination, and in particular to a graphite phase carbon nitride doped bismuth oxide composite electrode material and a preparation method and application thereof. Background Art
[0002] The scarcity of freshwater resources has seriously affected the sustainable development of social economy. - ) and sodium ions (Na + ) are common ions in water bodies and are widely found in seawater, industrial wastewater and domestic sewage. When the concentration of chloride ions and sodium ions in water is too high, it will bring a series of environmental and health problems. Chloride ions are highly corrosive and can cause serious corrosion to metal pipes and equipment, especially in industrial cooling systems and drinking water supply systems, which will accelerate the aging of infrastructure and increase maintenance costs. In addition, chloride ions also pose a potential threat to aquatic ecosystems. Excessive chloride ions can destroy the living environment of aquatic organisms and lead to water quality deterioration. More seriously, chloride ions react with organic matter during drinking water treatment and may produce harmful products such as trihalomethanes (THMs), which have been shown to be associated with a variety of cancers and reproductive health problems. Sodium ions are also one of the most common cations in water bodies. Their excessive presence can have a negative impact on human health, especially for patients with hypertension. In addition, excessive sodium ions can increase the total dissolved solids (TDS) content of water bodies, making the water unsuitable for drinking. In agriculture, excessive sodium ions in irrigation water can also lead to soil salinization, destroy soil structure, reduce crop yields, and ultimately affect the long-term productivity of farmland.
[0003] In this context, the importance of seawater desalination technology and industrial wastewater treatment technology has become increasingly prominent. At present, there are many types of water treatment and desalination technologies. Commonly used desalination methods include distillation, reverse osmosis (RO) and ion exchange. Although these technologies have been widely used, they also have obvious disadvantages. Distillation has extremely high energy consumption and requires a lot of heat energy to evaporate water, which makes it expensive, especially in large-scale desalination. Reverse osmosis relies on high pressure to push water through a semipermeable membrane. Not only does it consume a lot of energy, but the membrane material is easily corroded by chloride ions, which reduces its service life, requires frequent replacement and has high maintenance costs. Although ion exchange can effectively remove ions, the regeneration of the resin requires chemical reagents (such as acid or alkali), which leads to secondary pollution, and is less efficient when treating high-salinity water. In contrast, capacitive deionization (CDI) technology has become an important development direction in the field of water treatment due to its low energy consumption, high efficiency and environmental protection. CDI technology uses electrodes to adsorb ions in water and achieves desalination at low voltage, with energy consumption far lower than reverse osmosis and distillation. At the same time, CDI does not require chemical reagents to regenerate electrodes, avoiding secondary pollution, and is simple to operate and has low equipment costs. In addition, the renewability and long service life of CDI electrode materials make it more economical in long-term operation. The adsorption capacity of CDI mainly depends on electrode materials. However, current traditional electrode materials still have many shortcomings in ion removal efficiency, material stability, etc., especially when removing ions such as chloride ions and sodium ions, they show low selectivity and adsorption efficiency. Summary of the invention
[0004] In view of this, the present application provides a graphite phase carbon nitride doped bismuth oxide composite electrode material and its preparation method and application. The preparation method is simple and convenient, and the prepared composite electrode material is low-cost, which can effectively overcome the defects of the above-mentioned prior art.
[0005] The first aspect of the present application provides a method for preparing a graphite phase carbon nitride doped bismuth oxide composite electrode material, comprising the following steps:
[0006] G C 3 N 4 with Bi 2 O 3 The mixture is evenly mixed and calcined to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material.
[0007] Specifically, take gC 3 N 4 and Bi 2 O 3 The composite was placed in a mortar and ground thoroughly to obtain the composite, which was then placed in a ceramic crucible and calcined in a muffle furnace to obtain graphite phase carbon nitride doped bismuth oxide gC 3 N 4@Bi 2 O 3 The composite material was ground thoroughly in a mortar and pestle for later use.
[0008] Graphitic carbon nitride (gC 3 N 4 ) is an emerging two-dimensional material with unique photocatalytic properties and high specific surface area, which can effectively adsorb charged ions. 2 O 3 ) is a semiconductor material with good ion exchange capacity and electrochemical stability. In terms of cost, gC 3 N 4 and Bi 2 O 3 The raw materials are simple and easy to obtain, low in price, and can be prepared on a large scale. 3 N 4 @Bi 2 O 3 The material can not only improve the adsorption efficiency of chloride ions and sodium ions in the process of capacitive deionization, but also significantly enhance the cycle stability and conductivity of the electrode, thereby achieving high-efficiency desalination, providing a new solution for the field of water treatment.
[0009] Preferably, the method specifically comprises the following steps:
[0010] According to the mass ratio of 1:(1-4), gC 3 N 4 with Bi 2 O 3 The mixture is mixed evenly and calcined at 500-600° C. for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material.
[0011] Preferably, the gC 3 N 4 Made by calcining melamine.
[0012] Preferably, the gC 3 N 4 The specific preparation process is: the melamine is calcined at 500-600°C for 4-6 hours to obtain gC 3 N 4 .
[0013] Specifically, a certain amount of melamine was weighed, placed in a ceramic crucible, and calcined in a muffle furnace to obtain a bright yellow product. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0014] The second aspect of the present application also provides a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is a graphite phase carbon nitride doped bismuth oxide composite electrode material prepared by the above method.
[0015] The third aspect of the present application also provides a method for preparing an electrode plate, characterized in that the above-mentioned graphite phase carbon nitride doped bismuth oxide composite electrode material is used, comprising the following steps:
[0016] The graphite phase carbon nitride doped bismuth oxide composite electrode material, conductive carbon black, and polyvinylidene fluoride are fully ground in a mortar and put into a beaker, and an appropriate amount of N-methylpyrrolidone solvent is added. The slurry is stirred into a uniform slurry on a magnetic stirrer, and the slurry is evenly applied to a titanium plate with a scraper, and the slurry is dried in an oven to obtain an electrode plate.
[0017] Preferably, the amount ratio of the graphite phase carbon nitride doped bismuth oxide composite electrode material, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone solvent is 0.8g:0.1g:0.1g:2mL.
[0018] A fourth aspect of the present application also provides an electrode plate, which is an electrode plate prepared by the above method.
[0019] The fifth aspect of the present application further provides an application of the above-mentioned electrode plate in capacitive deionization and desalination, comprising the following steps:
[0020] Place the electrode plate in a capacitive deionization device, apply a certain voltage, pass a NaCl solution of a certain concentration, and use a conductivity meter to detect the change in conductivity in the solution in real time; when the adsorption reaches the peak value, reverse the voltage to release ions, realize the regeneration function, and achieve the effect of cyclic desalination.
[0021] Specifically, gC 3 N 4 @Bi 2 O 3 The positive electrode is made to adsorb chloride ions; the activated carbon is made into the negative electrode to adsorb sodium ions to achieve the purpose of desalination of water.
[0022] Preferably, the applied voltage is 1.0-1.6V; or
[0023] The concentration of NaCl is 500 mg / L; or
[0024] The adsorption capacity of the electrode plate is 32.15 mg / g, and after ten cycles, the electrode plate still has good regeneration performance.
[0025] Compared with the prior art, this application has the following beneficial effects:
[0026] 1. This application uses a high temperature calcination method to prepare a graphite phase carbon nitride doped bismuth oxide gC 3 N 4 @Bi 2 O 3 The composite electrode material is easy to operate and low in cost. After high-temperature calcination, bismuth oxide is effectively embedded in the pore structure of carbon nitride, which significantly increases the specific surface area and specific capacitance of the composite material. In addition, the surface of the composite material is rich in active functional groups, which greatly improves the Cl - 、Na + The adsorption activity of plasma shortens the adsorption time and significantly increases the adsorption capacity.
[0027] 2. The graphite phase carbon nitride doped bismuth oxide gC of the present application 3 N 4 @Bi 2 O 3 The composite electrode material is significantly superior to a single material in terms of electrical adsorption capacity and has the characteristics of recycling and reuse; after ten cycles of use, the electrical adsorption capacity of the composite electrode material can still be maintained at more than 90%, showing excellent stability and durability.
[0028] 3. The graphite phase carbon nitride doped bismuth oxide composite electrode material of the present application has abundant sites and attachment points, providing additional pseudocapacitance, which is beneficial to improve the electron transfer efficiency and electrical adsorption capacity; and the preparation method provided by the present application is simple and convenient, with low cost; under a certain voltage and flow rate, gC 3 N 4 @Bi 2 O 3 The composite electrode material is a Faraday capacitor that absorbs chloride ions, and the activated carbon is a double-layer capacitor that absorbs sodium ions, thereby achieving the effect of removing sodium chloride. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 gC prepared in Example 2 of the present application 3 N 4 @Bi 2 O 3 XRD patterns of composite materials;
[0031] Figure 2 gC prepared in Example 2 of the present application 3 N4 @Bi 2 O 3 SEM images of the composite materials;
[0032] Figure 3 gC prepared in Example 2 of the present application 3 N 4 @Bi 2 O 3 Electrical adsorption-desorption performance curve of composite materials. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the application. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technical method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0035] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0036] In the following examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0037] The bismuth oxide used in the following examples is commercial bismuth oxide, the activated carbon used is commercial activated carbon, and the conductive carbon black used is commercial conductive carbon black.
[0038] The graphite phase carbon nitride used in the following examples is commercial graphite phase carbon nitride; or it is prepared by calcining melamine in a muffle furnace, and the calcination parameters are the same as those disclosed in the prior art, that is, heating to 550° C. at a heating rate of 5° C. / min and calcining for 4 hours.
[0039] Example 1
[0040] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0041] (2) 1g gC 3 N 4 and 1g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0042] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0043] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.2V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 19.52mg / g.
[0044] Example 2
[0045] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0046] (2) 1g gC 3 N 4 and 2g Bi 2 O 3Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0047] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0048] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.2V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 32.15mg / g.
[0049] Figure 1 gC prepared in Example 2 of the present application 3 N 4 @Bi 2 O 3 XRD patterns of composite materials; Figure 2 gC prepared in Example 2 of the present application 3 N 4 @Bi 2 O 3 SEM images of the composite materials; Figure 3 gC prepared in Example 2 of the present application 3 N 4 @Bi 2 O 3 Electrical adsorption-desorption performance curve of composite materials.
[0050] Example 3
[0051] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0052] (2) 1g gC 3 N 4 and 3g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0053] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0054] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.2V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 23.24mg / g.
[0055] Example 4
[0056] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0057] (2) 1g gC 3 N 4and 4g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0058] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0059] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.2V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 22.31mg / g.
[0060] Example 5
[0061] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0062] (2) 1g gC 3 N 4 and 2g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0063] (3)gC 3 N4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0064] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.0V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 18.31mg / g.
[0065] Example 6
[0066] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0067] (2) 1g gC 3 N 4 and 2g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0068] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0069] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.4V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 27.43mg / g.
[0070] Example 7
[0071] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0072] (2) 1g gC 3 N 4 and 2g Bi 2 O 3 Put it in a mortar and grind it thoroughly to obtain a composite material, which is then placed in a ceramic crucible and heated to 550° C. in a muffle furnace for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material, which is fully ground in a mortar and set aside.
[0073] (3)gC 3 N 4 @Bi 2 O 3 Composite electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 @Bi 2 O 3 The composite electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were added in 0.8 g, 0.1 g, and 0.1 g, respectively, and were fully ground in a mortar and put into a beaker. 2 mL of N-methylpyrrolidone (NMP) solvent was added and placed on a magnetic stirrer to stir it into a uniform slurry. The slurry was evenly applied to a titanium plate with a scraper, placed in an oven, and dried at 80°C for 12 h to obtain an electrode plate for use.
[0074] (4) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.6V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 26.38mg / g.
[0075] Comparative Example 1
[0076] (1) Weigh 20 g of melamine and place it in a ceramic crucible, and heat it to 550°C in a muffle furnace for 4 hours. The product is bright yellow. 3 N 4 Powder, take it out and grind it thoroughly in a mortar for later use.
[0077] (2)gC 3 N 4 Electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 (i.e. gC 3 N 4 Electrode material, conductive carbon black, polyvinylidene fluoride (PVDF) (0.8g, 0.1g, 0.1g) were added respectively in a mortar and ground thoroughly, then put into a beaker, 2mL of N-methylpyrrolidone (NMP) solvent was added, and the mixture was placed on a magnetic stirrer to stir into a uniform slurry. The slurry was evenly applied onto a titanium plate with a scraper, and the plate was placed in an oven and dried at 80°C for 12h to obtain an electrode plate for use.
[0078] (3) In the desalination performance test of the electrode plate (the electrode plate is placed in a capacitive deionization device, a certain voltage is applied, a NaCl solution of a certain concentration is introduced, and the conductivity change in the solution is detected in real time by a conductivity meter; when the adsorption reaches a peak value, the voltage is reversed to release ions, realize the regeneration function, and achieve the effect of cyclic desalination), the voltage applied across the electrode is 1.2V, the electrolyte is a NaCl aqueous solution with a volume of 50ml and a concentration of 500mg / L, and the electrical adsorption capacity is 10.6mg / g.
[0079] Test Case
[0080] Specifically, the assembly process of the capacitor deionization device is as follows: the glass plate, the silicone gasket, the gC 3 N 4 @Bi 2 O 3 The electrode plates, separators, activated carbon electrode plates, silicone gaskets and glass plates are assembled in order and fixed with special screws.
[0081] Specifically, the capacitor deionization system consists of a capacitor deionization device, a sodium chloride solution, a liquid storage bottle, a constant current peristaltic circulation pump, a DC regulated power supply, and a conductivity meter, and a computer is used to monitor the conductivity change in real time. More specifically, the sodium chloride solution is placed in the liquid storage bottle, and each device is connected together by a water pipe to form a closed loop. The constant current peristaltic circulation pump is turned on, and the flow rate of the constant current peristaltic circulation pump is 40mL / min. The sodium chloride liquid (the initial concentration of the sodium chloride solution is 500mg / L) enters the bottom of the capacitor deionization device from the liquid storage bottle, flows through the inside of the device, and flows back to the liquid storage bottle from the top layer of the capacitor deionization device to form a cycle. The positive and negative poles of the DC regulated power supply are respectively connected to the positive and negative titanium plates, and a certain power supply voltage is applied to charge the capacitor deionization module for electrical adsorption desalination. After the adsorption is completed, the positive and negative poles are reversed to form a discharge stage. During the discharge process, the ions are desorbed back to the original solution at the positive and negative poles, forming an adsorption / desorption (charge and discharge) experiment. The conductivity meter detects the conductivity of the sodium chloride solution in the storage bottle in real time, records the conductivity value at fixed time, and saves it in the computer.
[0082] Table 1 is the test results of Examples 1-7
[0083] Example <![CDATA[g-C 3 N 4 with Bi 2 O 3 Quality Ratio]]> Voltage V Salt adsorption capacity mg / g Example 1 1:1 1.2 19.52 Example 2 1:2 1.2 32.15 Example 3 1:3 1.2 23.24 Example 4 1:4 1.2 22.31 Example 5 1:2 1.0 18.31 Example 6 1:2 1.4 27.43 Example 7 1:2 1.6 26.38
[0084] From the data in Table 1, it can be seen that through Examples 1-4, gC 3 N 4 and Bi 2 O 3 The effect of different ratios on the desalination capacity can be seen from Table 1. When the mass ratio is 1:2, the peak value is reached and the salt adsorption capacity is 32.15 mg / g.
[0085] It can be concluded from Examples 5-7 that the desalination capacity increases significantly with increasing voltage, which is attributed to the enhancement of the electric field force. However, when the voltage exceeds 1.2V, the adsorption capacity gradually decreases, which is due to the hydrolysis caused by excessive voltage. The corresponding salt adsorption capacities at voltages of 1.0V, 1.4V, and 1.6V are 18.31mg / g, 27.43mg / g, and 26.38mg / g, respectively. Therefore, under the conditions of a mass ratio of 1:2 and an applied voltage of 1.2V, gC 3 N 4 @Bi 2 O 3 The desalination efficiency of the composite electrode is optimal (such as Figure 3 shown).
[0086] Compared with Comparative Example 1, Examples 1-7 show that pure gC 3 N 4 Electrode and gC 3 N 4 @Bi 2 O 3By comparing the composite electrodes, it can be seen that the desalination efficiency is significantly improved from 10.6 mg / g to 32.15 mg / g.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a graphite phase carbon nitride doped bismuth oxide composite electrode material, characterized in that: The following steps are involved: The g-C3N4 and Bi2O3 are uniformly mixed and calcined to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material.
2. The method for preparing the graphite phase carbon nitride doped bismuth oxide composite electrode material according to claim 1, characterized in that: The specific steps include: The g-C3N4 and Bi2O3 were uniformly mixed in a mass ratio of 1:(1-4), and calcined at 500-600°C for 4 hours to obtain a graphite phase carbon nitride doped bismuth oxide composite electrode material.
3. The method for preparing the graphite phase carbon nitride doped bismuth oxide composite electrode material according to claim 1, characterized in that: The g-C3N4 is prepared by calcining melamine.
4. The method for preparing the graphite phase carbon nitride doped bismuth oxide composite electrode material according to claim 3, characterized in that: The specific preparation process of the g-C3N4 is as follows: the melamine is calcined at a temperature of 500-600° C. for 4-6 hours to obtain g-C3N4.
5. A graphite phase carbon nitride doped bismuth oxide composite electrode material, characterized in that: A graphite phase carbon nitride doped bismuth oxide composite electrode material prepared by the method described in any one of claims 1 to 4.
6. A method for preparing an electrode plate, characterized in that: The graphite phase carbon nitride doped bismuth oxide composite electrode material according to claim 5 comprises the following steps: The graphite phase carbon nitride doped bismuth oxide composite electrode material, conductive carbon black, and polyvinylidene fluoride are fully ground in a mortar and put into a beaker, and an appropriate amount of N-methylpyrrolidone solvent is added. The slurry is stirred into a uniform slurry on a magnetic stirrer, and the slurry is evenly applied to a titanium plate with a scraper, and the slurry is dried in an oven to obtain an electrode plate.
7. The method for preparing an electrode plate according to claim 6, characterized in that: The amount ratio of the graphite phase carbon nitride doped bismuth oxide composite electrode material, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone solvent is 0.8g:0.1g:0.1g:2mL.
8. An electrode plate, characterized in that: An electrode plate prepared by the method according to claim 6 or 7.
9. An application of the electrode plate according to claim 8 in capacitive deionization and desalination, characterized in that: The following steps are involved: Place the electrode plate in a capacitive deionization device, apply a certain voltage, pass a NaCl solution of a certain concentration, and use a conductivity meter to detect the change in conductivity in the solution in real time; when the adsorption reaches the peak value, reverse the voltage to release ions, realize the regeneration function, and achieve the effect of cyclic desalination.
10. Application of the electrode plate according to claim 9 in capacitive deionization and desalination, characterized in that: The applied voltage is 1.0-1.6V; or The concentration of NaCl is 500 mg / L; or The adsorption capacity of the electrode plate is 32.15 mg / g, and after ten cycles, the electrode plate still has good regeneration performance.
Citation Information
Cited By
Graphite phase carbon nitride modified electrode and preparation method and application thereof
CN121192187A